Alternative Management Regimes for multiple species fisheries - Chungsoo Kim (Kiel Institute of World Economics (IfW); ZBW – Leibniz Information Centre for Economics, 1981)
This empirical study examines welfare gains and losses that would result from alternative fishery management regimes. In an application to the North Sea demersal fisheries, the study shows that these fishery resources can give rise to large economic rent. Under an optimal management regime, the rent can be as high as three quarters of harvesting cost. As present, however, political conflicts make it unlikely that an efficiency-oriented fishery regime will be installed soon. Policy-makers appear to be unaware of the welfare cost of alternative fishery policies. This study tries to fill this void. As a guide of the formulation of fishery policies, it evaluates and compares four alternative fishery management regimes. The economic rent is estimated for each of these regimes. These estimates provide both a cardinal as well as an ordinal ranking of the alternative policies.
Keywords: 330